2021
DOI: 10.20473/jebis.v7i1.24818
|View full text |Cite
|
Sign up to set email alerts
|

Cash Waqf Linked Sukuk: Issues, Challenges and Future Direction in Indonesia

Abstract: Cash Waqf Linked Sukuk (CWLS) is the first innovation sukuk-based modern waqf fundraising development issued by the Indonesian government in 2020. People who prefer to channel their social funds in zakat, infaq, and shodaqah make CWLS less desirable. This paper evaluates the issues, challenges and future direction from the issuance of the CWLS series SWR001 by the Indonesian government. This study used systematic literature review analysis and used Publish or Perish software with Google Scholar as the database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
(14 reference statements)
0
9
0
1
Order By: Relevance
“…Some previous studies related to cash waqf intention will be explored and supported in this study (Azizi et al, 2019;Dennis et al, 2018;Kasri & Chaerunnisa, 2020;Niswah et al, 2020;Niswah et al, 2019;Osman & Muhammed, 2017;Purnomowati et al, 2020;Syafira et al, 2020;Zabri & Mohammed, 2018;Haidlir et al 2021). However, there are only limited studies related to CWLS (Baiti & Syufaat, 2021;Hiyanti et al, 2020;Paul et al, 2021;Tanjung & Windiarto, 2021;Yasin, 2021). Tanjung and Windiarto (2021) explain that the integration between cash waqf and Sukuk can increase the benefits of the fund.…”
Section: Previous Studies On Cash Waqf Intentionmentioning
confidence: 67%
See 2 more Smart Citations
“…Some previous studies related to cash waqf intention will be explored and supported in this study (Azizi et al, 2019;Dennis et al, 2018;Kasri & Chaerunnisa, 2020;Niswah et al, 2020;Niswah et al, 2019;Osman & Muhammed, 2017;Purnomowati et al, 2020;Syafira et al, 2020;Zabri & Mohammed, 2018;Haidlir et al 2021). However, there are only limited studies related to CWLS (Baiti & Syufaat, 2021;Hiyanti et al, 2020;Paul et al, 2021;Tanjung & Windiarto, 2021;Yasin, 2021). Tanjung and Windiarto (2021) explain that the integration between cash waqf and Sukuk can increase the benefits of the fund.…”
Section: Previous Studies On Cash Waqf Intentionmentioning
confidence: 67%
“…Another study showed that religiosity positively impacts attitude, Islamic egalitarianism and behavioural intention (Dennis et al, 2018). However, as this CWLS is a relatively new program, it found obstacles related to limited partners and literacy (Yasin, 2021). In this digital era, literacy can be broadened through technology and waqf can be accessed easily through financial technology.…”
Section: Previous Studies On Cash Waqf Intentionmentioning
confidence: 98%
See 1 more Smart Citation
“…Waqf's concerns have been important because of the efforts of modern scholars, who have shown the benefits of Waqf's activities in contemporary society, including its applications and the challenges involved. Most prior studies have shown that waqf cash is an efficient tool to be an alternative to reducing poverty because these projects need vast amounts that the government cannot get altogether (Yasin, 2021). Two forms of waqf and Sukuk combinations are being developed, namely Cash Waqf Linked Sukuk and Sukuk Linked Waqf.…”
Section: Sukuk Linked Waqfmentioning
confidence: 99%
“…The CWLS investors collection is still facing some obstacles such as: lack of understanding of the Moslem community about cash waqf (Napitupulu et al, 2021), lack of public trust in cash waqf management institutions and lack of willingness to donate cash waqf ( (Sukmana, 2020); (Shukor et al, 2017); (Yasin, 2021); (Kasri & Chaerunnisa, 2021)). Based on previous studies, factors such as Age, Income, and Education are the main determinants of understanding of the Moslem community about waqf-based financial institutions in Indonesia ( (Efrizon, 2008); (Khan et al, 2020); (Shukor et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%